Functional expression, monodispersity and conformational changes in the SBMV virus viral VPg on binding TFE - Mariutti, R. B. [UNESP]; Caruso, I. P. [UNESP]; Ullah, A. [UNESP]; De Morais, F. R. [UNESP]; Rehders, D.; Arni, R. K. [UNESP] (Elsevier, 2016)
Southern bean mosaic virus (SBMV) RNA purified from infected plants was used for cloning the viral genome-linked protein (VPg) and was subsequently expressed in Escherichia coli. Circular dichroism (CD), dynamic light scattering (DLS) and saturation transfer difference (STD) by nuclear magnetic resonance (NMR) measurements were employed to determine the degree of monodispersity and to investigate the conformational changes in the absence and presence of trifluoroethanol (TFE) which indicated increased helical content with increasing concentration of TFE. 8-Anilino-1-naphthalenesulfonic acid (ANS) was used as a probe to compare the unfolding regions of the protein before and after addition of TFE. The results indicated that although the TFE concentration influences VPg folding, it does not play a role in nucleotide binding and that the local solvent hydrophobicity causes significant conformational changes.
Keywords: Expression; Purification; Viral genome-linked protein; VPg